Shallow and uneven progress towards global financial transparency: evidence from the Financial Secrecy Index - Wojcik, D (Elsevier, 2023)
The global financial crisis and leaked documents such as the Panama Papers highlighted the important role of financial secrecy in the global economy. Although international initiatives pressing for more transparency have gained strength, there is little knowledge on how the map of financial secrecy has changed over the past decade and why. We use the internationally recognised Financial Secrecy Index and analyse its five editions between 2011 and 2020. We find that financial transparency related to international standards and cooperation improved much more than transparency in the arguably more substantive areas of ownership registration, transparency of legal entities, as well as tax and financial regulation. Second, we document convergence of financial transparency among jurisdictions. While some of the most secretive countries and jurisdictions became more transparent, many with higher transparency in 2011 became relatively more secretive by 2020. This convergence is driven mainly by the most secretive countries and jurisdictions becoming more internationally cooperative. Third, we map the heterogeneity of financial secrecy across the world and classify 71 countries and jurisdictions into five groups, which cut across conventional geographical divisions, highlighting the need to study secrecy in specific contexts. They do, however, show that while OECD countries are relatively more transparent, their former colonies, with continued links with and dependency on former colonial powers, exhibit little improvement. Put together, our findings show that while some progress towards global financial transparency has been achieved, it is shallow and very uneven, with convergence potentially replacing a race-to-thebottom dynamic.